VISI PROFETIK PUISI YANG KARYA ABDUL WACHID B.S. - Dimas Indianto (IBDA` : Jurnal Kajian Islam dan Budaya, 2013)
This paper is a library research which analyzes the poem anthology‘Yang’ of Abdul Wachid B.S. There are three dimensions from thepoems; the first is transcendental which consists of (a) pray and honesty,(b) tauhid, (c) piousness, (d) faith, (e) zikir, (f) the unity of man and God.The second is liberation; (a) understanding, (b) anti-harassment, (c) position-awareness, and (d) avoiding others from accident. The third is humanism;(a) helping each other, (b) obeying the rule, (c) affection.